Модель выбора набора ИТ-сервисов для конечных пользователей - Левыкин, Виктор Макарович; Юрьев, Иван Алексеевич (НТУ "ХПИ", 2016)
В статье рассматриваются вопросы выбора набора ИТ-сервисов для конечных пользователей информационной системы. Разработана модель выбора набора ИТ-сервисов для конечных пользователей. Описаны все элементы разработанной модели и их взаимодействие в процессе выбора набора ИТ-сервисов. Представлена иерархическая структура критериев оценки ИТ-сервиса. Представлена реализация разработанной модели с применением метода парных сравнений.

The article deals with the selection of a set of IT services for end-users of information systems. The model of selecting a set of IT services to end users was developed. All the elements of the developed model was describe, and their interaction in the process of selecting a set of IT services. A set of high-quality IT services means their best set of features and characteristics that meet the stated needs of the enterprise. Enterprise requirements are determined by its business strategy. IT services is a set of software, which has the same functionality corresponds to a plurality of end user requirements. This set is determined by the requirements of end-users to support business processes, which are performed as part of their job descriptions. A paper presents a hierarchical structure of criteria for evaluating IT service. Presents the implementation of the developed model using the method of paired comparisons.
Model selection of the set of IT services for end users
Keywords: бизнес-процессы; информационная система; ИТ-инфраструктура предприятия; сервис-ориентированная архитектура; метод парных сравнений; IT service; selection; information system; end-users